Impact of Genetic Engineering on Agriculture Applications - Hariraman, Kavitha (Recent Research Reviews Journal, 2022)
The primary goal of modern agriculture is to increase the amount and quality of crop production. Bacteria and other small organisms, plants, and animals can all be genetically modified. Genetic engineering helps the scientists to even transfer the targeted genes of one plant to another. This is also referred to as Genetically Modified Organisms (GMOs). Plants can be genetically modified to acquire particular traits. Even though this process differs from traditional breeding, it boosts the effectiveness in crop yield. The increased crop yields, lowered costs for food or drug production, reduced pesticide requirement, improved nutrient composition as well as food quality, increased pest and disease resistance, increased food security, and medical benefits are considered as the major objectives of genetic engineering in agriculture domain. This research study discusses about the genetically modified crops, their processes, advantages and the novel state-of-the-art cropping trends.